The Provision of Social Welfare for Individuals with Limited Opportunities at Chong Sarika Sub-district Administrative Organization, Phatthananikhom District, Lopburi Province - Suwannarong, Soontaree; Prasopsak, Wasita Kerdphon; Subruangthong, Waraporn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The research aims to study the level of opinions toward the provision of social welfare for individuals with limited opportunities at Chong Sarika Sub-District Administrative Organization, Phatthananikhom District, Lopburi Province. The research population was 157 individuals with limited opportunities who reside in the area. They were recruited by a simple sampling method. The data collection tool was a 36-item questionnaire with a reliability level of 0.875. The data were analyzed using percentage, mean, and standard deviation. The findings indicated that, overall, the level of opinions regarding the provision of social welfare for individuals with limited opportunities in the Chong Sarika Sub-District Administrative Organization was at a high level. When considering individual issues ranked from the highest to the lowest means, addressing the issues of poverty and limited opportunities was at the highest mean, followed by education, safety in life and properties, housing, health and hygiene, and recreation respectively.